A Bio‐inspired Platform to Modulate Myogenic Differentiation of Human Mesenchymal Stem Cells Through Focal Adhesion Regulation. Issue 3 (1st October 2012) - Yu, Haiyang; Tay, Chor Yong; Pal, Mintu; Leong, Wen Shing; Li, Huaqiong; Li, Hai; Wen, Feng; Leong, David Tai; Tan, Lay Poh
Abstract The use of human mesenchymal stem cells (hMSCs) in cardiac‐tissue engineering has gained widespread attention and many reports have shown that matrix compliance, micro/nano‐patterns could be some of the important biophysical cues that drive hMSCs differentiation. Regardless of the type of biophysical induction cues, cells mainly explore their environment via focal adhesion (FA) and FA plays an important role in many cellular behaviours. Therefore, it is hypothesized that FA modulation through materials manipulation could be an important cue for modulation that would result in the stem cell lineage commitment. In this work, the FA of hMSCs is modulated by a novel microcontact printing method using polyvinyl alcohol as a trans‐print media which can successfully print proteins on soft polydimethylsiloxane (PDMS). The FA is successfully modified into dense FA and elongated FA by micropatterning square and rectangular patterns on 12.6 kPa PDMS respectively. Additionally, the combined effects of stiffness of PDMS substrates (hard (308 kPa), intermediate (12.6 kPa)) and FA patterning on hMSCs differentiation are studied. The results indicate that dense FA does not induce myogenesis while elongated FA can promote cytoskeleton alignment and further myogenesis on PDMS with intermediate stiffness of 12.6 kPa. However, on stiff substrate (308 kPa), with or without patterns, the cytoskeleton alignment and myogenesis are not obvious. This demonstrates for the first time that it is possible to induce the differentiation of hMSCs by regulating the FA using a materials platform even in the absence of any biochemical factors. It also shows that there is a synergistic effect between FA regulation and matrix stiffness that results in a more specific and higher up‐regulated myogenesis. This platform presents a new chemical/biological‐free method to engineer the myogenic differentiation of hMSCs.